Enhancing Legume Ecosystem Services through an Understanding of Plant–Pollinator Interplay - Suso, María J.; Bebeli, Penelope J.; Christmann, Stefanie; Mateus, Célia; Negri, Valeria; Pinheiro de Carvalho, Miguel A. A.; Torricelli, Renzo; Veloso, Maria M. (Frontiers in Plant Science, 2016)
Legumes are bee-pollinated, but to a different extent. The importance of the plant-pollinator interplay (PPI), in flowering crops such as legumes lies in a combination of the importance of pollination for the production service and breeding strategies, plus the increasing urgency in mitigating the decline of pollinators through the development and implementation of conservation measures. To realize the full potential of the PPI, a multidisciplinary approach is required. This article assembles an international team of genebank managers, geneticists, plant breeders, experts on environmental governance and agro-ecology, and comprises several sections. The contributions in these sections outline both the state of the art of knowledge in the field and the novel aspects under development, and encompass a range of reviews, opinions and perspectives. The first three sections explore the role of PPI in legume breeding strategies. PPI based approaches to crop improvement can make it possible to adapt and re-design breeding strategies to meet both goals of: 1) optimal productivity, based on an efficient use of pollinators, and 2) biodiversity conservation. The next section deals with entomological aspects and focuses on the protection of the “pest control service” and pollinators in legume crops. The final section addresses general approaches to encourage the synergy between food production and pollination services at farmer field level. Two basic approaches are proposed: a) Farming with Alternative Pollinators (FAP) and b) Crop Design System (CDS).